The vulvar microbiome in lichen sclerosus and high-grade intraepithelial lesions - Pagan, Lisa; Huisman, Bertine W.; van der Wurff, Michelle; Naafs, Rosanne G. C.; Schuren, Frank H. J.; Sanders, Ingrid M. J. G.; Smits, Wiep Klaas; Zwittink, Romy D.; Burggraaf, Jacobus; Rissmann, Robert; Piek, Jurgen M. J.; Henderickx, Jannie G. E.; et al. (Frontiers in Microbiology, 2023)
The role of the vulvar microbiome in the development of (pre)malignant vulvar disease is scarcely investigated. The aim of this exploratory study was to analyse vulvar microbiome composition in lichen sclerosus (LS) and vulvar high-grade squamous intraepithelial lesions (HSIL) compared to healthy controls.Women with vulvar lichen sclerosus (n=10), HSIL (n=5) and healthy controls (n=10) were included. Swabs were collected from the vulva, vagina and anal region for microbiome characterization by metagenomic shotgun sequencing. Both lesional and non-lesional sites were examined. Biophysical assessments included trans-epidermal water loss for evaluation of the vulvar skin barrier function and vulvar and vaginal pH measurements.Results: Healthy vulvar skin resembled vaginal, anal and skin-like microbiome composition, including the genera Prevotella, Lactobacillus, Gardnerella, Staphylococcus, Cutibacterium and Corynebacterium. Significant differences were observed in diversity and richness between vulvar skin of healthy controls and LS patients. Compared to the healthy vulvar skin, vulvar microbiome composition of both LS and vulvar HSIL patients was characterized by significantly higher proportions of respectively Papillomaviridae (p=0.045) and Alphapapillomavirus (p=0.002). In contrast, the Prevotella genus (p=0.031) and Bacteroidales orders (p=0.038) were significantly less abundant in LS, as was the Actinobacteria class (p=0.040) in vulvar HSIL. While bacteria and viruses were most abundant, fungal and archaeal taxa were scarcely observed. Trans-epidermal water loss was higher in vulvar HSIL compared to healthy vulvar skin (p=0.043).This study is the first to examine the vulvar microbiome through metagenomic shotgun sequencing in LS and HSIL patients. Diseased vulvar skin presents a distinct signature compared to healthy vulvar skin with respect to bacterial and viral fractions of the microbiome. Key findings include the presence of papillomaviruses in LS as well as in vulvar HSIL, although LS is generally considered an HPV-independent risk factor for vulvar dysplasia. This exploratory study provides clues to the aetiology of vulvar premalignancies and may act as a steppingstone for expanding the knowledge on potential drivers of disease progression.